The Effect of Local Government Spending For Education and Health on Grdp and Human Development Index in North Labuhanbatu District - Ayu Angelina Pasaribu*; Sutejo Perangin Angin; Irsad Irsad; Dede Ruslan (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to analyze and determine the effect of government spending on education and health on GRDP and the human development index in North Labuhanbatu District. The data used in this research is secondary data in 2017-2021. The analysis tool used is path analysis. The software used to carry out the analysis is IBM SPSS Version 20. The results of the analysis show that an increase in government spending on education has a positive and insignificant effect on GRDP in North Labuhanbatu Regency . These results are in accordance with the hypothesis but not significant in terms of triggering an increase in GRDP. This could be due to the fact that educated graduates are still not optimal in absorbing labor in accordance with the demand for available jobs. The increase in government spending on health has a positive and significant effect on GRDP in North Labuhanbatu District. It can be concluded that there is a significant impact from the increase in the health sector budget spending on increasing GRDP in North Labuhanbatu Regency. Because GRDP will increase if everyone enjoys maximum health facilities.